Validation of a Cell-Based Assay for Detection of Active Shiga Toxins Produced by Escherichia coli in Water - Anna C. Hughes (International Journal of Environmental Research and Public Health, 2020)
Shiga toxin-producing Escherichia coli (STEC) causes a wide spectrum of diseases, including hemorrhagic colitis and hemolytic uremic syndrome (HUS). Almost 5% of STEC infections result from waterborne exposures, yet there is no test listed in the EPA’s current Selected Analytical Methods for the detection of active Shiga toxins (Stxs) in water. In this study, a HeLa cell-based assay is validated for the detection of metabolically active Stxs produced by STEC in water, including tap, bottled, and pond water. Active Stxs are detected even when the number of Stx-producing bacteria is less than 0.4 CFU/mL and the assay performance is not affected by background flora or chlorine in the water. This assay is not only as simple and affordable as cell-free assays but also detects active holotoxins without the use of live animals. In addition, the assay is designed for use in multi-well formats, making it ideal for high-throughput screening of water samples and therefore useful for environmental public health surveillance programs to reduce human risk of infection with STEC.